Visualization of synchronization zone on the Bloch sphere through an anti-PT-symmetric electrical circuit - M. Kim; Y. Yang; Y. S. Gui; C.-M. Hu (AIP Advances, 2022)
This work reports an analysis of the anti-parity-time (APT) symmetry system produced by pure dissipative coupled passive electric oscillators. Through spectral and time-domain measurements, the complex eigenfrequencies of the APT-symmetric system were measured. Interesting physics, such as exceptional points, APT-symmetry breaking transitions, and frequency synchronization with explicitly defined phase differences, were observed. Most importantly, we found that synchronous signals span the equator of the Bloch sphere. Therefore, our methodology functions as an analogon understructure to explore APT-symmetric systems.